Comparative efficacy of intravenous levetiracetam and phenytoin in status epilepticus: a systematic review and meta-analysis of randomized controlled trials (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Status epilepticus (SE) is a neurological emergency, with the current guidelines for second-line anticonvulsants may include phenytoin, levetiracetam, valproic acid, and phenobarbital. However, some studies suggest that levetiracetam may be better at stopping seizures in SE. This study aimed to compare the efficacy of intravenous (IV) levetiracetam and phenytoin in SE. METHODS We searched PubMed, ScienceDirect, Cochrane, and Google Scholar for randomized controlled trials (RCTs) on administering IV levetiracetam or phenytoin in patients with SE. RCTs were screened using eligibility criteria, and their quality was assessed using the Cochrane risk of bias tool. Heterogeneity was assessed using the I² test, and publication bias was evaluated using Egger’s test. All analyses were performed using Review Manager version 5.4 (The Cochrane Collaboration, UK) and Stata 17 (StataCorp LLC, USA). RESULTS 12 RCTs involving 2,137 patients (1,099 receiving levetiracetam) met the inclusion criteria. Pooled analysis showed that levetiracetam therapy had a significantly higher rate of seizure cessation than phenytoin (RR: 1.10, 95% CI = 1.05−1.14, p = 0.02, I² = 51%). Less adverse events were observed in the levetiracetam group (9.34%) than in the phenytoin group (11.62%; RR: 0.82, 95% CI = 0.66–1.02, p = 0.07). However, there was no significant difference regarding IV levetiracetam or phenytoin administration with the incidence of admission to critical care (RR: 1.01; 95% CI = 0.93–1.10, p = 0.80) and mortality (RR: 1.08; 95% CI = 0.54–2.15; p = 0.82). CONCLUSIONS IV levetiracetam was significantly better in the cessation of seizures in SE patients than phenytoin.